Clutch control systems - WINDSOR; HARRY M (1984)
A vehicle automatic clutch control has an engine speed sensor that produces an electrical signal indicative of engine speed, an electrical reference signal generator that produces a reference signal, a throttle position sensor that produces a signal indicative of throttle opening. The throttle signal is summed with the reference signal to produce a modified reference signal which is then compared with the engine speed signal by a comparator that produces an error signal. The error signal is used for controlling a clutch actuator that operates the clutch to vary the engagement of the clutch to alter the engine speed and equalize the modified reference signal and engine speed signal and thus maintain a substantially constant engine speed until the clutch is fully engaged.